A Mixed Method Analysis of Mental Toughness in Elite and Sub-elite Male and Female Tennis Players in Pakistan - Masum, Rubina (Advances in Social Sciences Research Journal, 2014)
The study examines the potential relationship between mental toughness and performance among elite and sub-elite tennis players in Karachi. 118 participants (3 male seasoned performers, 42 Elite male, 32 sub-elite male, 16 elite female, and 25 sub-elite females) were selected through purposive sampling. The mean age of the seasoned performers was 34 years, elite players’ 22.98 years (SD 7.55) and of sub-elite players was 22.42 years (SD 2.50). Qualitative data was collected by adapting the scale “Athletes “how tough are you”, Enders, Pamela Lynn (2007) in three sessions: i) individual semi- structured interviews of the 3 seasoned performers and ii) a focus group comprised of 8 elite and7 sub-elite players, and iii) an unstructured interview with the senior vice-President of Sindh Tennis Association. Psychological Performance Inventory- Alternative (Golby et al., 2007) was employed as a quantitative measure of mental toughness of 115 participants. Findings for qualitative data revealed that 3 seasoned performers considered ability to deal with pressure, ability to deal with pressure, focus, visualization, Confidence, ability to deal with negative talk, motivation and consistency to be crucial factors for tennis. Elite players regarded focus, and “fear of losing” to be critical aspects in comparison to sub-elite players who attributed motivation and routine practice to be crucial factors for tennis. Interview with the vice-president considered focus and monetary rewards to be decisive factors pertaining to the success of tennis players. Quantitative analysis was comprised of Cornbach Alpha reliability that was measured =.852 for 14 items (PPI-A, 2007). Findings of Independent sample t tests demonstrated that there was a significant difference between elite and sub-elite players on the measures of MT t =7.864, p=<.000, df =113. Independent sample t test was indicated t =6.622p=<.000, df =113 for gender differences in relation to MT. Stepwise multiple regression analyses on the components of mental toughness also indicated a significant difference among elite and non-elite tennis players Self-Belief, and Determination (B-=.086, t= 4.701, p<.000) and (B=.066, t=3.162, p<.000) respectively. On the basis of these results it can be deduced that properties of MT can be linked to predicting success in tennis.